Risk of Latent Tuberculosis Infection Reactivation in Patients Treated with Tumor Necrosis Factor Antagonists: A Five-Year Retrospective Study - Işıl Deniz Alıravcı; Pınar Mutlu; Sibel Oymak; Ufuk Ilter Guney; Oguzhan Keskin (Tropical Medicine and Infectious Disease)
Background: This study aims to reveal the demographic and clinical data of patients receiving TNF-α blockers, to compare the characteristics of those who received latent tuberculosis infection (LTBI) treatment and those who did not, and to evaluate and determine potential risk factors for developing active TB disease. Methods: A systematic retrospective study was conducted in a tertiary university hospital examining all patients receiving at least one TNF-α blocker between January 2019 and October 2024. The incidence of tuberculosis (TB) was analyzed across various TNF-α blocker medications in patients, both with and without LTBI treatment. Results: A total of 519 patients had TNF-α blockers: 452 (87.09%) underwent TST, 193 (37.1%) underwent booster TST, and 33 (6.3%) underwent IGRA/TST; 362 (69.7%) were treated for LTBI, and 7 (1.3%) developed TB. Comparing all TNF-α blockers, adalimumab showed a higher risk of TB. Patients with and without LTBI treatment did not significantly differ in TB incidence after biologic therapy. Conclusions: The incidence of TB in people taking TNF-α blockers was higher compared to the incidence in the general population. LTBI screening, including both TST and IGRA, should be performed with TST and IGRA tests, and LTBI-positive individuals should be started on preventive treatment. However, it should not be forgotten that active TB disease may also develop in LTBI-negative individuals.